Pandangan Pelaku Ekonomi tentang Pentingnya Peranan Uang dalam Proses Interaksi dan Transaksi Harian - Hafif Setiawan; Salsabila Rahman; Melani Rusli; Muhammad Arfan Harahap (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to describe the perspectives of economic actors regarding the importance of money in daily interactions and transactions. Money, as a medium of exchange, not only facilitates the transfer of goods and services but also shapes more efficient and structured economic behavior. In everyday activities, economic actors view money as an instrument that provides value certainty, transactional convenience, and flexibility in managing needs and expenditures. The role of money is also understood as a factor influencing socio-economic relationships, as interactions between individuals are often grounded in transactional processes that require trust and universally accepted exchange values. Furthermore, the development of payment technologies has broadened economic actors’ understanding of money, especially within the context of digitalized transactions. This study illustrates that money is not merely a transactional tool but also a crucial element in shaping the socio-economic dynamics of modern society. The findings are expected to contribute to microeconomic discussions related to how economic actors utilize money as a fundamental instrument in daily economic activities.